ANÁLISE DA EVOLUÇÃO DO EMPREGO FORMAL DO MUNICIPIO DE CRUZ ALTA - Arruda, Jônatas; Pacheco, Jussiano R.; Lucca, Emerson J.; Kohler, Romualdo; Trennepohl, Dilson; Sperotto, Pamela A. (Salão do Conhecimento, 2013)
Resumo